The diversity of Class II transposable elements in mammalian genomes has arisen from ancestral phylogenetic splits during ancient waves of proliferation through the genome - Hellen, Elizabeth H.B.; Brookfield, John F.Y. (Oxford University Press, 2012)
DNA transposons make up three percent of the human genome, roughly the same percentage as genes. However, due to their inactivity, they are often ignored in favour of the more abundant, active, retroelements. Despite this relative ignominy, there are a number of interesting questions to be asked of these transposon families. One particular question relates to the timing of proliferation and inactivation of elements in a family. Does an ongoing process of turnover occur, or is the process more akin to a life cycle for the family, with elements proliferating rapidly before deactivation at a later date?